A photosensitive monomer, a preparation method and application thereof
Patent Information
- Application Number
- CN202611079512.0
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2026-07-21
- Publication Date
- 2026-10-20
AI Technical Summary
[0013]因此为解决现有技术中缺少一种低介电常数、高绝缘性、高感光活性及优异存储稳定性的新型感光性材料的问题,本发明提供一种感光性单体、其制备方法与应用
本发明将感光基团通过化学键合方式接入聚合物侧链,其光敏性优于采用物理共混方式制备得到的正性光刻胶组分;主要表现在以下几个方面:
Smart Images

Figure FT_1 
Figure FT_2 
Figure FT_3
Abstract
Description
Technical Field
[0001] This invention relates to a photosensitive monomer, its preparation method and application, belonging to the field of photoresist photosensitive agent technology. Background Technology
[0002] Positive photoresists dominate photolithography due to their advantages such as high resolution, wide development tolerance, and good process compatibility. Currently, the positive photoresists widely used in industry are mainly based on the diazonaphthoquinone (DNQ) photosensitive system. Their core photosensitive mechanism is as follows: the -N=N double bond in the diazonaphthoquinone molecule absorbs ultraviolet light of a specific wavelength (such as the 365 nm i-line), undergoing a Wolff rearrangement reaction to generate a highly reactive enone intermediate. This intermediate further reacts with water in the system to form indanone carboxylic acid, thus significantly increasing the solubility of the photoresist in the exposed area in the alkaline developer, creating a clear dissolution contrast with the unexposed area, resulting in a positive pattern after development. Therefore, the effective introduction of the -N=N double bond and its photochemical activity are the core factors determining the photosensitive performance of the photoresist.
[0003] However, traditional positive photoresists are generally prepared by physical blending, mixing small-molecule diazonoquinone photosensitizers with phenolic resin matrices, which has the following inherent drawbacks that are difficult to overcome: Migration of Small Molecule Photosensitive Agents: Diazonaphthoquinone, as a small molecule compound, has limited compatibility with phenolic resin matrices. During long-term storage of photoresist, small molecule photosensitive agents are prone to phase separation, exudation, or recrystallization, leading to decreased uniformity of the photoresist formulation, resulting in problems such as particle defects, reduced resolution, and increased line edge roughness (LER). In severe cases, it can cause complete photoresist failure, significantly shortening the product's shelf life. Furthermore, during processes such as exposure, baking, and development, the migration of small molecule photosensitive agents can also lead to uneven photosensitive agent concentration distribution, further deteriorating the quality of the photolithographic pattern.
[0004] Insufficient electrical performance: The cross-linked network formed after the physical blend system is cured exhibits chemical inhomogeneity. Phase separation regions introduce numerous interface defects and ion migration channels, leading to an increase in the dielectric constant and a decrease in the insulation performance of the photoresist-cured film. In high-frequency, high-voltage devices and advanced packaging processes, this defect significantly affects the signal transmission speed and reliability of the devices, limiting their application in high-end microelectronics.
[0005] Poor process compatibility: In subsequent high-temperature curing, ion implantation and other process steps, the residual small molecule photosensitizer is prone to thermal decomposition or volatilization. The generated gas may cause pattern deformation, peeling or pinhole defects, affecting the yield of the device.
[0006] To address the aforementioned issues, those skilled in the art have attempted to graft the diazonoquinone photosensitive group onto the polymer backbone via chemical bonding, thereby fundamentally inhibiting the migration of small molecule photosensitizers.
[0007] For example, Chinese invention patent CN119511634B discloses a method for modifying a photoresist composition, relating to the field of photoresist technology. The photoresist is a type of positive photoresist, comprising a phenolic polymer resin, a diazonoquinone-type photoinitiator, a solvent, and additives. This invention uses a multi-carbon-based enol compound as a precursor to prepare a diazonoquinone sulfonate-type photosensitive compound. The aldehyde group carried in the diazonoquinone sulfonate-type photosensitive compound is used to graft the photoinitiator-phenolic resin coupling product with amine additives via a Schiff base reaction, adjusting its dissolution inhibition effect, thereby enhancing key properties of the photoresist such as resolution, etching resistance, and edge roughness after exposure and development.
[0008] However, existing chemically bonded photosensitive resin technology still has many bottlenecks and cannot meet the comprehensive requirements of advanced microelectronics manufacturing: First, the improvement in electrical performance is limited. In existing technologies, even when phase separation defects are eliminated through chemical bonding, the dielectric constant (@1kHz) of the cured film typically remains at a relatively high level of 3.51-3.55, and the surface resistivity is generally below 10¹. 5 The dielectric constant is Ω / sq, and the breakdown voltage is less than 600 V. This is mainly because existing technologies lack systematic optimization of the distribution density of polar functional groups along the polymer side chain. Excessive polar residual groups still lead to an increase in dielectric constant and cannot completely block ion migration channels, making it difficult to achieve a synergistic improvement in low dielectric constant and high insulation. It is also unable to effectively reduce parasitic capacitance and crosstalk between wirings, thus restricting the electrical performance and long-term reliability of the chip back-end process.
[0009] Secondly, insufficient photosensitivity limits production capacity. In existing chemically bonded photosensitive resins, the grafting of photosensitive groups often alters the surrounding chemical environment, leading to a decrease in the light absorption efficiency of the -N=N double bond and a slower Wolff rearrangement reaction rate. The photoreaction rate constant of typical existing chemically bonded systems under 365 nm ultraviolet light is only 1-2 times that of traditional physically blended systems, resulting in long exposure times that severely restrict the production efficiency of photolithography processes and make it difficult to meet the needs of large-scale industrial production.
[0010] In addition, existing technologies also have problems such as difficulty in accurately controlling the grafting rate, wide distribution of resin molecular weight, complex synthesis process, and high production cost, which further limit their industrial application in the field of high-end photoresists.
[0011] In summary, no novel photosensitive material has yet been developed in this field that can simultaneously achieve low dielectric constant, high insulation, high photosensitivity, and excellent storage stability.
[0012] How to optimize the distribution of photosensitive groups and polar functional groups on polymer side chains through molecular structure design, so as to significantly improve electrical properties while ensuring photosensitivity and achieve synergistic enhancement of the two, remains one of the technical challenges that urgently need to be solved in the field of positive photoresists. Summary of the Invention
[0013] Therefore, in order to address the problem of the lack of a novel photosensitive material with low dielectric constant, high insulation, high photosensitivity and excellent storage stability in the existing technology, this invention provides a photosensitive monomer, its preparation method and application.
[0014] The technical solution of the present invention to solve the above-mentioned technical problems is as follows: A photosensitive monomer, the structure of which is shown in formula (Ⅰ):
[0015] Ⅰ In formula (Ⅰ), R1 is independently selected from one of hydrogen atoms, alkyl derivatives and phenyl derivatives; X is independently selected from either O or S atoms; R2 is independently selected from one of the following: hydrogen atom, C1-C8 alkyl group, C3-C8 cycloalkane derivative, benzene ring, benzene ring derivative and group -X-R3; R3 is independently selected from one of the following structures: .
[0016] The present invention also provides stereoisomers, geometric isomers, tautomers, enantiomers and diastereomers of the above-mentioned photosensitive monomers.
[0017] The present invention also provides the application of the above-mentioned photosensitive monomer in the preparation of photoresist.
[0018] The present invention also provides a method for preparing the above-mentioned photosensitive monomer, comprising the following steps: (1) Dissolve phenolic substituted styrene and diazonoquinone, mix with non-metallic ion base, and react to obtain intermediate reactants; (2) Mix the intermediate reactant obtained in step (1) with the halogen-free acid, and separate them to obtain the final product; The phenolic substituted styrene substances are selected from one of p-hydroxystyrene, o-hydroxystyrene, m-hydroxystyrene, 4-vinylguaiacol, 3,4-dihydroxystyrene, 1,3-dihydroxystyrene, 4,4'-(ethylene-1,1-diyl)diphenol, eugenol, p-hydroxycinnamic acid, 4,4'-dihydroxystyrene and its derivatives, and p-mercaptostyrene and its derivatives.
[0019] Preferably, the molar ratio of the phenolic substituted styrene, diazonaphthoquinone, and non-metallic ion base is 1:1-1.1:1-1.1.
[0020] Preferably, the diazonoquinone is selected from 2-diazo-1-naphthol-5-sulfonyl chloride and 2-diazo-1-naphthol-4-sulfonyl chloride.
[0021] Preferably, the non-metallic ionic base is selected from one or more of amine compounds and nitrogen-containing heterocyclic compounds.
[0022] More preferably, the amine compound includes methylamine, ethylamine, trimethylamine, triethylamine, and tetramethylamine hydroxide; The nitrogen-containing heterocyclic compounds include pyridine and its derivatives, and imidazole and its derivatives.
[0023] Preferably, the halogen-free acid is selected from one or more of sulfuric acid, nitric acid, phosphoric acid, formic acid, acetic acid, propionic acid, oxalic acid, and malonic acid.
[0024] Preferably, the reaction in step (1) includes a first heat preservation and a second heat preservation.
[0025] More preferably, the temperature of the first heat preservation is -20 to 20 ℃.
[0026] More preferably, the heat preservation time is 2-4 hours.
[0027] More preferably, the temperature of the secondary insulation is 30-80 ℃.
[0028] More preferably, the secondary heat preservation time is 3-5 hours.
[0029] Preferably, the separation method in step (2) includes the anti-solvent method; The antisolvent used in the aforementioned antisolvent method is water.
[0030] More preferably, the temperature of the antisolvent method is -20 to 80 °C.
[0031] More preferably, the temperature of the antisolvent method is -10 to 70 °C.
[0032] More preferably, the temperature of the antisolvent method is 10-40 °C.
[0033] More preferably, the volume ratio of the antisolvent to the solvent system of the reactants to be separated in the antisolvent method is 5-100:1.
[0034] More preferably, the antisolvent method further includes a filtration step.
[0035] More preferably, the separation method further includes a step of washing the separated material until it is neutral.
[0036] The beneficial effects of this invention are as follows: This invention incorporates photosensitive groups into polymer side chains via chemical bonding, resulting in superior photosensitivity compared to positive photoresist components prepared through physical blending. This is primarily manifested in the following aspects: This invention effectively fixes photosensitive groups onto the polymer backbone by adjusting the chemical bonding method, avoiding ineffective migration or concentration loss during the reaction process. It fundamentally solves the problem of formulation failure caused by easy exudation, recrystallization or migration of small molecule photosensitive agents, and extends the effective shelf life of photoresist.
[0037] This invention chemically bonds photosensitive groups to the side chains, and the resulting cross-linked network formed after curing a photoresist composition has a highly uniform chemical environment, which reduces the dielectric constant and improves the insulation performance. Attached Figure Description
[0038] Figure 1 The image shows the infrared characterization of p-hydroxystyrene. Figure 2 The infrared characterization image of the photosensitive monomer PHS-PAC of Synthetic Example 1 is shown. Figure 3 This is a photoreaction kinetic diagram of the cured film in Example 1; Figure 4 The image shows the photoreaction kinetics of the cured film in Comparative Example 1. Detailed Implementation
[0039] The principles and features of the present invention are described below with reference to the accompanying drawings. The examples given are only for explaining the present invention and are not intended to limit the scope of the present invention.
[0040] Unless otherwise specified, all raw materials used in the specific embodiments of the present invention are purchased from conventional commercial channels.
[0041] Synthesis Example 1: Preparation of Photosensitive Monomer 1 6 g of p-hydroxystyrene (PHS, Mr = 120.15 g / mol) and 13.53 g of 2-diazo-1-naphthol-5-sulfonyl chloride (Mr = 270.69 g / mol) were dissolved in 100 mL of N,N-dimethylformamide (DMF), and 5.08 g of triethylamine (Mr = 101.6 g / mol) was added. The temperature of the reaction system was controlled at -10 °C, and the reaction was carried out for 2 h. Then, the temperature was raised to 30 °C and the reaction was continued for 3 h. Oxalic acid was added to adjust the pH of the system to 5-6, and the mixture was filtered.
[0042] The filtrate was added dropwise to 1000 g of water to settle. After stirring for 2 h at room temperature, the mixture settled, filtered, and vacuum dried at 50 °C for 48 h to obtain the photosensitive monomer 1 PHS-PAC.
[0043] The reaction process is shown in the following equation: .
[0044] Synthesis Example 2: Preparation of Photosensitive Monomer 2 7.5 g of 4-vinylguaiacol (HMS, Mr=150.17) and 13.53 g of 2-diazo-1-naphthol-5-sulfonyl chloride (Mr=270.69 g / mol) were dissolved in 150 mL of a mixed solvent of dioxane and acetone (volume ratio 1:1). 10 g of 20%wt tetramethylammonium hydroxide (TMAH) aqueous solution was added. The reaction system was controlled at 20 °C and reacted for 4 h. The temperature was raised to 80 °C and reacted for 3 h. Acetic acid was added to adjust the pH of the system to 5-6, and the mixture was filtered.
[0045] The filtrate was added dropwise to 1500 g of water to settle. After stirring for 2 h at room temperature, the mixture settled, filtered, and then vacuum dried at 40 °C for 72 h to obtain photosensitive monomer 2.
[0046] Synthesis Example 3: Preparation of Photosensitive Monomer 3 6 g of p-hydroxystyrene (PHS, Mr=120.15 g / mol) and 13.53 g of 2-diazo-1-naphthol-4-sulfonyl chloride (Mr=270.69 g / mol) were dissolved in 100 mL of γ-butyrolactone. 7.76 g of 1,8-diazabicyclo[5.4.0]undec-7-ene (DBU, Mr=152.24 g / mol) was added. The temperature of the reaction system was controlled at -20 °C. After reacting for 2 h, the temperature was raised to 40 °C and the reaction was continued for 3 h. Anhydrous acetic acid was added to adjust the pH of the system to 5-6, and the mixture was filtered.
[0047] The filtrate was added dropwise into 2000 g of water to settle. After stirring for 2 h at room temperature, the mixture settled, filtered, and vacuum dried at 45 °C for 60 h to obtain photosensitive monomer 3.
[0048] Synthesis Example 4: Preparation of Photosensitive Monomer 4 13.61 g of 3,4-dihydroxystyrene (Mr=136.15 g / mol) and 27.08 g of 2-diazo-1-naphthol-4-sulfonyl chloride (Mr=270.69 g / mol) were dissolved in 200 mL of N-methylpyrrolidone. 12.3 g of N,N-dimethylpyridine (Mr=122.17 g / mol) was added. The temperature of the reaction system was controlled at 0 °C. After reacting for 3 h, the temperature was raised to 60 °C and the reaction was continued for 5 h. Anhydrous formic acid was added to adjust the pH of the system to 5-6, and the mixture was filtered.
[0049] The filtrate was added dropwise into 2000 g of water to settle. After stirring for 2 h at room temperature, the mixture settled, filtered, and vacuum dried at 45 °C for 60 h to obtain photosensitive monomer 4.
[0050] Synthesis Example 5: Preparation of methacrylate copolymer 1 5 g of methacrylic acid (Mr=86.09 g / mol), 9 g of hydroxyethyl methacrylate (Mr=130.14), 2 g of PHS-PAC (Mr=354.38), and 24 g of benzyl methacrylate (BzMA,Mr=176.21) were weighed and mixed, and dissolved in propylene glycol methyl ether acetate (PGMEA) to prepare a solution with a solute content of 20 wt%. 2% (by mass) of azobisisobutyronitrile (AIBN) initiator was added to the solution, and the reaction was carried out at 80 °C for 10 h under nitrogen protection. After the reaction was completed, the solution was poured into n-hexane to precipitate the solid, filtered, and the solid was dried under vacuum at 40 °C for 24 h to obtain a pale yellow solid product. Its molecular weight (Mw) was 9070, acid value was 77.59 mgKOH / g, and dispersion (PDI) was 1.96.
[0051] Synthesis Example 6: Preparation of methacrylate copolymer 2 Weigh out 5 g of methacrylic acid, 7 g of hydroxypropyl methacrylate, 4 g of the photosensitive monomer from Synthesis Example 2, and 30 g of adamantyl methacrylate, mix them, and dissolve them in 200 g of propylene glycol monomethyl ether. Add 3% (by mass) of AIBN initiator to the mixture, and react at 80 °C for 5 h under nitrogen protection. After the reaction is complete, pour the solution into n-hexane to precipitate the product, filter it, and dry the solid under vacuum at 50 °C for 48 h to obtain a pale yellow solid product. The molecular weight (Mw) was 8000, the acid value was 65.96 mgKOH / g, and the dispersion (PDI) was 1.89.
[0052] Synthesis Example 7: Preparation of methacrylate copolymer 3 10 g of methacrylic acid, 8 g of octyl methacrylate, 3 g of the photosensitive monomer from Synthesis Example 3, and 25 g of dicyclopentenyl methacrylate were weighed and mixed, and dissolved in 150 g of diethylene glycol methyl ethyl ether. 4% (by mass) of AIBN initiator was added, and the mixture was reacted at 80 °C for 8 h under nitrogen protection. After the reaction was complete, the solution was poured into n-hexane to precipitate, filtered, and the solid was dried under vacuum at 45 °C for 36 h to obtain a pale yellow solid product. Its molecular weight (Mw) was 5300, acid value was 135.67 mgKOH / g, and dispersion (PDI) was 2.04.
[0053] Synthesis Example 8: Preparation of methacrylate copolymer 4 2 g of methacrylic acid, 9 g of p-hydroxystyrene, 6 g of the photosensitive monomer from Synthesis Example 4, and 29 g of methyl methacrylate were weighed and mixed, then dissolved in 160 g of propylene glycol methyl ethyl ether. 1.5% (by mass) of 2,2'-azobis(2,4-dimethylpentanonitrile) (V-65) initiator was added, and the mixture was reacted at 60 °C for 20 h under nitrogen protection. After the reaction was complete, the solution was poured into n-hexane to precipitate the solid, which was then filtered. The solid was dried under vacuum at 50 °C for 16 h to obtain a pale yellow solid product. Its molecular weight (Mw) was 9800, its acid value was 25.53 mgKOH / g, and its dispersion (PDI) was 2.24.
[0054] Comparative Synthesis Example 1 5 g of methacrylic acid (Mr=86.09), 9 g of methyl methacrylate (Mr=130.14), and 24 g of benzyl methacrylate (BzMA, Mr=176.21) were weighed and mixed. 2% (by mass) of AIBN initiator was added to the mixture. The mixture was reacted at 80 °C for 10 h under nitrogen protection to synthesize the resin represented by formula (Ⅱ) (average molecular weight 9000). After the reaction was complete, the mixture was cooled to room temperature, and 2 g of a commercially available photoacid-producing agent (B-1) was added. The mixture was stirred until completely dissolved, and the solution was poured into n-hexane to precipitate. The precipitate was filtered, and the solid was dried under vacuum at 40 °C for 24 h.
[0055]
[0056] II Comparative Synthesis Example 2 5 g of methacrylic acid (Mr=86.09), 9 g of methyl methacrylate (Mr=130.14), and 24 g of benzyl methacrylate (BzMA, Mr=176.21) were weighed and mixed. 2% (by mass) of AIBN initiator was added to the mixture. The mixture was reacted at 80 °C for 10 h under nitrogen protection to synthesize the resin represented by formula (II) above (average molecular weight 9000). After the reaction was complete, the mixture was cooled to room temperature, and 4 g of a commercially available photoacid-producing agent (B-1) was added. The mixture was stirred until completely dissolved, and the solution was poured into n-hexane to precipitate. The precipitate was filtered, and the solid was dried under vacuum at 40 °C for 24 h.
[0057] Examples 1-10 and Comparative Examples 1-4: Positive Photoresist Compositions In the examples and comparative examples, the following reference numerals are used to represent the corresponding chemical substances: methacrylate copolymer A-1: Product of Synthetic Example 5; A-2: Product of Synthetic Example 6; A-3: Product of Synthetic Example 7; A-4: Product of Synthetic Example 8; Photoacid-producing agents B-1: condensate of 1,1,1-tris(p-hydroxyphenyl)ethane (1.0 mol) and 1,2-naphthoquinone diazido-5-sulfonyl chloride (2.3 mol); <c>surfactants FZ-2122, DOWSIL™; <d>Adhesive γ-isocyanate propyltriethoxysilane, Shin-Etsu Chemical Industry Co., Ltd. <e>solvent E-1: Propylene glycol monomethyl ether acetate (20 °C, 3.75 mmHg); E-2: Diethylene glycol dimethyl ether.
[0058] Example 1 100 g of the methacrylate copolymer (A-1) containing the photosensitive monomer synthesized in Synthesis Example 5, 0 g of the photosensitive monomer (B-1), 0.4 g of the surfactant (C), and 0.6 g of the adhesion promoter (D) were added to a container. Then, solvent (E) was added to dissolve the copolymer, resulting in a positive photoresist composition.
[0059] Examples 2-10 and Comparative Examples 1-4 were prepared in the same manner as in Example 1, except that the types and amounts of each component were changed as shown in Tables 1 and 2.
[0060] Table 1. Ingredients and Dosage of Examples 1-10
[0061] Table 2. Components and Dosage of Comparative Examples 1-4
[0062] Performance tests of the positive photoresist compositions provided in the experimental examples, embodiments, and comparative examples The positive photoresist compositions prepared using the above examples and comparative examples were evaluated for the following performance: (1) Evaluation of photosensitivity The powders obtained from Synthetic Example 5 and Comparative Synthetic Example 1 were ground with KBr at a mass ratio of 1:100 in an agate mortar for 1 min until uniformly distributed. The powders were then pressed into tablets using a four-column hydraulic press. The resulting tablets were then subjected to infrared spectroscopy using a Brook Alpha II infrared spectrometer, with readings taken at 2120 cm⁻¹. -1 The absorbance value at that point was then used, with an illuminance of 0.21 mJ / cm². 2 Infrared measurements were performed every 40 seconds after UV irradiation, and readings were taken at 2120 cm⁻¹. -1 The absorbance values at the specified locations were used to plot the photosensitivity of the material based on the Lambert-Beer law, as shown below.< / e> < / d> < / c> Figure 3 , 4 As shown.
[0063] (2) Volume resistivity and surface resistivity On a 5*5 cm glass substrate, the photoresist compositions of Examples 1-10 and Comparative Examples 1-4 were coated using a spin coater, and then pre-baked at 100 °C for 2 min using a hot plate to form a cured film with a thickness of 2.5 μm. The resulting cured film was then subjected to a cumulative irradiation dose of 1000 mJ / cm² using a Canon PLA-501F exposure unit (ultra-high pressure mercury lamp). 2 After exposure, the film was heated at 230 °C for 1 h in a clean drying oven to obtain a cured film. The volume resistivity of the cured film was obtained according to GB / T 31838.2-2019; the surface resistivity of the cured film was obtained according to GB / T 1551-2021. The relevant test data are shown in Tables 3 and 4.
[0064] (3) Dielectric constant and breakdown voltage On a 5*5 cm glass substrate coated with an ITO conductive film, the edges were masked with 3 cm wide tape. After spin-coating the compositions of Examples 1-10 and Comparative Examples 1-4 using a spin coater, the substrate was pre-baked at 100 °C for 2 min using a hot plate to form a cured film with a thickness of 2.5 μm and dimensions of 2*2 cm. The cured film was then subjected to a cumulative irradiation dose of 1000 mJ / cm² using a Canon PLA-501F exposure unit (ultra-high pressure mercury lamp). 2 After exposure, the film was heated at 230 °C for 1 hour in a clean drying oven to obtain a cured film. The breakdown voltage of the cured film was obtained according to GB / T 1408.1-2016; the dielectric constant of the cured film was obtained according to GB / T 31838.6-2021. The relevant test data are shown in Tables 3 and 4.
[0065] Table 3. Results of Experiments in Examples 1-10
[0066] Table 4. Results of Comparative Examples 1-4
[0067] As can be seen from the results in Tables 3 and 4, since the positive photoresist composition of this invention uses the photosensitive monomer copolymer shown in Formula (I), the cured film of the obtained positive photoresist composition, compared with the cured films of the positive photoresist compositions formed in Comparative Examples 1-4 using copolymer raw materials with the structure shown in Formula (II) in Table 4, shows that this invention directly introduces specific photosensitive groups onto the resin backbone and optimizes the chain-linked distribution density of polar functional groups in the polymer side chains. Combined with electrical test data, the chemical bonding strategy successfully reduced the dielectric constant (@1kHz) significantly from 3.51-3.55 in the comparative examples to 2.53-2.95 (the maximum reduction is about 27%). At the same time, the uniform network structure blocks ion migration channels, increasing the volume resistivity to 2.85-2.94×10¹. 5 The breakdown voltage is stable above 650 V with a dielectric constant of Ω / sq. This synergistic improvement in low dielectric constant and high insulation effectively reduces parasitic capacitance and crosstalk between wirings, significantly enhancing the electrical performance and long-term reliability of the chip's back-end manufacturing process.
[0068] from Figure 1 and Figure 2 It can be seen from this that at 2300 cm -1 The presence of a distinct -N=N absorption peak nearby indicates the introduction of a photosensitive structure into the polymer, thus avoiding the durability issues of traditional blend systems. Furthermore, this characterization result is based on the product's photosensitive properties; the -N=N double bonds absorb ultraviolet light, leading to a Wolff rearrangement that alters the resin's solubility in the developer, ultimately forming the pattern.
[0069] Figure 3 and Figure 4 The reaction rate constants of Example 1 and Comparative Example 1 under 365 nm UV light are presented. The reaction rate constant of Example 1 is approximately 4.3 times that of the Comparative Example 1 system. This indicates that the chemical bonding strategy greatly accelerates the photodegradation process, significantly improving the efficiency of acid (or initiator) generation after exposure, thereby greatly shortening the reaction time and increasing the throughput of the photolithography process.
[0070] The above description is only a preferred embodiment of the present invention and is not intended to limit the present invention. Any modifications, equivalent substitutions, improvements, etc., made within the spirit and principles of the present invention should be included within the protection scope of the present invention.
Claims
1. A photosensitive monomer, characterized in that, The structure is shown in Equation I: Ⅰ In Formula I, R1 is independently selected from one of hydrogen atoms, alkyl derivatives, and phenyl derivatives; X is independently selected from either O or S atoms; R2 is independently selected from one of the following: hydrogen atom, C1-C8 alkyl group, C3-C8 cycloalkane derivative, benzene ring, benzene ring derivative and group -X-R3; R3 is independently selected from one of the following structures, 。 2. The method for preparing the photosensitive monomer according to claim 1, characterized in that, Includes the following steps: (1) Dissolve phenolic substituted styrene and diazonoquinone, mix with non-metallic ion base, and react to obtain intermediate reactants; (2) Mix the intermediate reactant obtained in step (1) with the halogen-free acid, and separate them to obtain the final product; The phenolic substituted styrene substances are selected from one of p-hydroxystyrene, o-hydroxystyrene, m-hydroxystyrene, 4-vinylguaiacol, 3,4-dihydroxystyrene, 1,3-dihydroxystyrene, 4,4'-(ethylene-1,1-diyl)diphenol, eugenol, p-hydroxycinnamic acid, 4,4'-dihydroxystyrene and its derivatives, and p-mercaptostyrene and its derivatives.
3. The preparation method according to claim 2, characterized in that, The molar ratio of the phenolic substituted styrene, diazonaphthoquinone, and non-metallic ionic base is 1:1-1.1:1-1.
1.
4. The preparation method according to claim 2, characterized in that, The diazonoquinone is selected from 2-diazo-1-naphthol-5-sulfonyl chloride and 2-diazo-1-naphthol-4-sulfonyl chloride.
5. The preparation method according to claim 2, characterized in that, The non-metallic ionic base is selected from one or more of amine compounds and nitrogen-containing heterocyclic compounds.
6. The preparation method according to claim 5, characterized in that, The amine compounds include methylamine, ethylamine, trimethylamine, triethylamine, and tetramethylamine hydroxide; The nitrogen-containing heterocyclic compounds include pyridine and its derivatives, and imidazole and its derivatives.
7. The preparation method according to claim 2, characterized in that, The halogen-free acid is selected from one or more of sulfuric acid, nitric acid, phosphoric acid, formic acid, acetic acid, propionic acid, oxalic acid, and malonic acid.
8. The preparation method according to claim 2, characterized in that, The reaction described in step (1) includes a first heat preservation and a second heat preservation; The temperature for the first heat preservation is -20 to 20 ℃; The duration of each heat preservation cycle is 2-4 hours; The temperature for the secondary insulation is 30-80℃; The secondary insulation time is 3-5 hours.
9. The preparation method according to claim 2, characterized in that, The separation method described in step (2) includes the anti-solvent method; The antisolvent used in the aforementioned antisolvent method is water.
10. The use of the photosensitive monomer according to claim 1 in the preparation of photoresist.
Citation Information
Patent Citations
A method for modifying a photoresist composition
CN119511634B